Doutor eu quero um medicamento genérico! uma análise da influência das marcas organizacionais sobre o risco percebido na prescrição de medicamentos genéricos - Yokoshiro, Paulo Roberto Aziz (2009)
The national prescription drug market has been trough several transformations. One of them come in the wake of the advent of generic products by bill 9.787 from the Fernando Henrique Cardoso administration. The reference pharmaceutical companies have attempted to establish their products in a competitive market through non-ethical prescription drugs, known as enhancend products. This paper analyzes the influence of the organization s brand as a marketing strategy on the risk perceived at the moment when generic drugs are prescribed by doctors in the city Salvador. To that end, a survey has been carried out according to the central theorem of the limit. The sample was no probabilística for convenience, with 101 responding doctors. The obtained conclusion contributes with the theory demonstrating that the value of the organization's brand can be a strategic alternative in the decrease of the risk perception in the market of generic medicines.